Antibody production and tolerance to the α-gal epitope as models for understanding and preventing the immune response to incompatible ABO carbohydrate antigens and for α-gal therapies - Galili, Uri (Frontiers in Molecular Biosciences, 2023)
This review describes the significance of the alpha-gal epitope (Galalpha-3Gabeta1-4GlcNAc-R) as the core of human blood-group A- and B-antigens (A and B-antigens), determines in mouse models the principles underlying the immune response to these antigens, and suggests future strategies for induction of immune-tolerance to incompatible A- and B-antigens in human allografts. Carbohydrate-antigens such as ABO antigens and the alpha-gal epitope differ from protein-antigens in that they do not interact with T-cells, but B-cells interacting with them require T-cell help for their activation. The alpha-gal epitope is the core of both A and B antigens and is ligand of the natural anti-Gal antibody which is abundant in all humans. In A and O individuals, anti-Gal clones (called anti-Gal/B) comprise >85% of the so called anti-B activity and bind to the B-antigen in facets that do not include fucose linked alpha1-2 to the core alpha-gal. As many as 1% of B-cells are anti-Gal B-cells. Activation of quiescent anti-Gal B-cells upon exposure to alpha-gal epitopes on xenografts and on some protozoa can increase titer of anti-Gal by 100-folds. alpha1,3Galactosyltransferase knockout (GT-KO) mice lack alpha-gal epitopes and can produce anti-Gal. These mice simulate human recipients of ABO incompatible human allografts. Exposure for 2-4 weeks of naïve and memory mouse anti-Gal B-cells to alpha-gal epitopes in heterotopically grafted wild-type (WT) mouse heart results in elimination of these cell and immune-tolerance to this epitope. Shorter exposures of 7 days of anti-Gal B-cells to alpha-gal epitopes in WT heart results in production of accommodating anti-Gal antibodies that bind to alpha-gal epitopes but do not lyse cells or reject graft. Tolerance to alpha-gal epitopes due to elimination of naïve and memory anti-Gal B-cells can be further induced by 2 weeks in-vivo exposure to WT lymphocytes or to autologous lymphocytes engineered to present alpha-gal epitopes by transduction of the alpha1,3galactosyltransferase genes. These mouse studies suggest that autologous human lymphocytes similarly engineered to present A- or B-antigens may induce corresponding tolerance in recipients of ABO-incompatible allografts. The review further summarizes experimental works which demonstrate efficacy of alpha-gal therapies in amplifying anti-viral and anti-tumor immune-protection and in regeneration of injured tissues.